Comment bâtir une prospective commune pour la gestion d'un fleuve transfrontalier ? L'exemple de L'Escaut. - Gabrielle Bouleau (VertigO)
The European Union recently adopted a common strategy to reach a good status of all aquatic ecosystems and plan a sustainable water management (the water framework directive, 23 Oct. 2000). For each watershed, it requires an economical analysis of stakes and possible options. This can give an opportunity to change methods of planning which have led to unsustainable practises, especially on the Schelde. How to build such a common vision when transboundary rivers are concerned? Pointing out what biases were responsible of unsustainability in the methods used in the past for water management planning, we propose alternative way of doing, using future studies and the examples of the Schelde.